Kingdom of Lesotho : Technical Assistance Report-Government Finance Statistics. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2022)
In response to a request from the authorities and as part of the Data for Decisions (D4D)1 funded project under the submodule for Fiscal and Debt reporting, a government finance statistics (GFS) technical assistance (TA) mission was held remotely with the Lesotho Ministry of Finance (MOF) during April 5-16, 2021. Previous TA missions under the Enhanced Data Dissemination Initiative (EDDI2) over the period spanning from 2016 to 2020 assisted the MOF to improve GFS compilation and dissemination for the budgetary central government (BCG) and inspired action to broaden data coverage to include local governments and extrabudgetary units (EBUs) with the aim to compile and disseminate consolidated general government GFS. Preliminary local government GFS have now been compiled, and data collected for selected state-owned enterprises (SOEs) and parastatals, including non-market SOEs that can now contribute to preliminary general government GFS to be compiled.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Lesotho, Kingdom of